Sustainable medicinal plant production - responses of Lamiaceae plants to organic acid elicitors spraying during environmental stress: A review - Ismail Mahmoud Ali Shahhat; Arbi Guetat; Salma Yousif Sidahmed Elsheik; Medhat Ahmed Abu-Tahon; Abdelrahman Talha Abdelwahab; Marwa Abdelfattah Awad (Plant Protection Science)
This article provides a review of recent studies on the extent to which the use of organic acid elicitors such as salicylic, jasmonic, humic and ascorbic acids has been successful in alleviating the exposure of Lamiaceae plants to unfavourable environmental conditions such as drought and salinity. Overall, the results concluded all organic acid elicitors enhanced the morphological and physiological characteristics of biochemical and secondary metabolite contents. These improvements have enabled plants of the Lamiaceae family to adapt to environmental stress conditions to some extent and survive, thus achieving sustainability in the production of plants of this family. It can be recommended to use salicylic acid in concentrations 0.5-2.5 mM, and it should not exceed it so as not to cause poisoning and disruption of the vital and physiological processes within the plant. In contrast, these plants have limited studies on the relationship between jasmonic acid/ascorbic acid and ascorbic acid. Since vitamins such as ascorbic acid are essential for plant metabolism and growth regulation, their effect on these plants remains unstudied at concentrations 2-10 mM under different abiotic stresses. Further research is needed to understand the impact of Nano-SA, JA, HA, ASA, and citric acid on Lamiaceae plants under various environmental stress conditions. Limited studies exist on the relationship between jasmonate/humic acid and Lamiaceae plants under abiotic stress. The Lamiaceae family needs more studies on adaptation to various environmental conditions and the toxicity of stimulants used to confront these conditions. This research contributes to improving agricultural practices in challenging environmental regions.